2021
DOI: 10.1177/10901981211019920
|View full text |Cite
|
Sign up to set email alerts
|

Stay Socially Distant and Wash Your Hands: Using the Health Belief Model to Determine Intent for COVID-19 Preventive Behaviors at the Beginning of the Pandemic

Abstract: Background The COVID-19 pandemic has quickly spread around the world, and since currently no treatments that are safe and effective for large groups of people nor a vaccine are available, the best way to prevent the illness is to avoid being exposed to the virus causing it. The purpose of this study was to examine the predictive effects of both demographic and psychosocial factors originating with the Health Belief Model on reported intent to adhere to COVID-19 preventive behaviors (e.g., social distancing, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 11 publications
(16 reference statements)
2
25
1
Order By: Relevance
“…In March 2020, Guidry et al, observed that 19.8% of the participants answered "somewhat likely" and 65.8% "extremely likely" in their tendency to avoid large gatherings compliance. 14 In addition, in our study, the rate was 31.5% in the first pandemic period for visiting family or friends, 51.3% in the middle of the pandemic, and currently 75.2%.…”
Section: Discussionsupporting
confidence: 42%
“…In March 2020, Guidry et al, observed that 19.8% of the participants answered "somewhat likely" and 65.8% "extremely likely" in their tendency to avoid large gatherings compliance. 14 In addition, in our study, the rate was 31.5% in the first pandemic period for visiting family or friends, 51.3% in the middle of the pandemic, and currently 75.2%.…”
Section: Discussionsupporting
confidence: 42%
“…It also provides an opportunity to study individual resilience amid health crises. Scholars across various disciplines wish to determine what shapes precautionary behaviors and builds individual resilience ( Guidry et al, 2021 ; Wang et al, 2021 ; Clark et al, 2022 ). According to their findings, social-demographic features are critical in determining resilience amid a health crisis.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…For patients with prolonged low titers, further protection and treatment strategies against COVID-19 warranted. We recommend that these patients continue to wear a face mask and wash their hands to prevent COVID-19 even after vaccination [ 7 , 8 ]. Fortunately, T-cell-mediated immune responses were detected even in patients during R-CHOP treatment with a combination therapy of anti-CD20 antibody and cytotoxic chemotherapy.…”
mentioning
confidence: 99%